Parents’ English Experience as The Induction of EFL Students’ English Competence - Dewi, Ambarsari Sukma; Rahmat Setiawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the role of parents’ English language experience in shaping the English competence of EFL (English as a Foreign Language) students. It focuses on how parental involvement, regardless of their English proficiency, supports their children’s English development. The research also explores how parents’ educational background, parent-child relationships, and the level of parental involvement contribute to children’s motivation and progress in learning English. Using a qualitative approach, this study investigates how parents with varying levels of English experience contribute to their children’s language learning. Data were collected through in-depth interviews with four 12th-grade students, selected based on their relevance to the study. These students come from families with different educational backgrounds and English language experience. The interviews were semi-structured, focusing on students’ experiences in learning English, the support they receive from their parents, and how their parents’ English language experience shapes their learning process. In addition to the interviews, documentation such as students’ report cards and parents’ salary slips were analyzed to provide context regarding the socio-economic background. The findings show that parental involvement, regardless of their English proficiency, plays a significant role in students’ English development. Parents with limited English experience still provide moral support, emphasize the importance of English for the future, and create a supportive learning environment. The study suggests that schools should enhance parental involvement by offering training and resources, particularly for parents with limited educational backgrounds and English experience, to improve the learning ecosystem and support English learning more effectively.